Surface-coated silicon-carbon composite, method for producing a surface-coated silicon-carbon composite, anode electrode and electrochemical

By coating the metal oxide layer on the surface of the silicon-carbon composite material of the lithium-ion battery anode, the problem of insufficient chemical stability during the manufacturing process is solved, and higher chemical and mechanical stability is achieved.

CN119547216APending Publication Date: 2025-02-28SELFOSS GRP GMBH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380045301.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-14
Filing Date
2023-04-14
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The complex surface structure of the anode of lithium-ion batteries is prone to chemical reactions with harmful compounds in the environment during the manufacturing process, resulting in insufficient chemical stability.

Method used

Silicon-carbon composite materials using porous carbon scaffolds and coated with metal oxide layers such as Al2O3 and LiAlO2 on the surface to improve chemical and mechanical stability.

Benefits of technology

Through the protection of the surface coating layer, the chemical and mechanical stability of the silicon-carbon composite material and the anode electrode is significantly improved, reducing unnecessary risk of chemical reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119547216A_ABST
    Figure CN119547216A_ABST
Patent Text Reader

Abstract

The present invention relates to a silicon-carbon composite material comprising a porous carbon scaffold comprising micropores and mesopores and having a total pore volume greater than 0.5 cm3 / g; a silicon content between 30% and 70%, including 30% and 70%; and a surface region having an at least partially coated first surface coating comprising at least one element of Li, B, Al, Si, P, Ti, Zr, Nb and / or W. The invention further relates to a method for producing such a surface-coated silicon-carbon composite material, an anode electrode and an electrochemical energy storage device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a surface-coated silicon-carbon composite material, which comprises a porous carbon support, wherein the porous carbon support comprises micropores and mesopores having a pore volume. In addition, the present disclosure relates to a method for manufacturing the surface-coated silicon-carbon composite material, an anode electrode and an electrochemical energy storage device. Background Art

[0002] Lithium-ion batteries are widely used and provide stored energy for different components. In particular, in electric and hybrid vehicles, such lithium-ion batteries provide electrical energy for vehicle components and powertrains. In such application scenarios, it is highly desirable to obtain a longer electric driving range, which can be achieved by increasing the capacity of the battery. The capacity of the battery can be increased by increasing the surface area of ​​the electrode. This can be achieved through more complex surface structures. Various methods are known for coating at least one current collector of the anode with silicon carbon to increase the area of ​​reversible lithium embedding and the number of lithium ions involved in the charging and discharging process. Such complex surface structures and coatings may easily react chemically with compounds in the environment (for example, during the manufacture of lithium-ion battery cells). In particular, during the filling process of the electrolyte of the lithium-ion battery cell, certain parts of the anode and its surface structure may be accidentally exposed to harmful substances (for example, oxidizing substances). Summary of the invention

[0003] The object of the present disclosure is to provide a silicon-carbon composite material with improved chemical stability and a method for producing a silicon-carbon composite material with improved chemical stability. This object is achieved by the subject matter of the independent claims. Further improvements of the subject matter of the independent claims are provided in the dependent claims.

[0004] According to one aspect of the present disclosure, a silicon-carbon composite material is disclosed. The silicon-carbon composite material can be used in an anode electrode and thus can be used in an electrochemical energy storage device, such as a lithium-ion battery cell or a lithium-ion battery.

[0005] The silicon-carbon composite material comprises a porous carbon scaffold having micropores and mesopores and a total pore volume greater than 0.5 cm 3 / g.

[0006] In addition, the porous carbon scaffold of the silicon-carbon composite may contain a plurality of particles for additional tuning of its chemical and mechanical properties. Providing additional particles within the porous carbon scaffold of the silicon-carbon composite may control the dynamics of lithium ions within the silicon-carbon composite.

[0007] The silicon-carbon composite material has a silicon content between 30% and 70% (inclusive), and a surface region at least partially coated with a first surface coating. The surface coating of the surface region of the silicon-carbon composite material contains at least one element of Li, B, Al, Si, P, Ti, Zr, Nb and / or W. The percentages mentioned in this application may be weight percentages or volume percentages relative to the silicon-carbon composite material.

[0008] In another aspect of the present invention, an anode electrode is provided, which comprises a surface-coated silicon-carbon material. The anode electrode preferably comprises a metal component, such as a metal foil. The silicon-carbon composite material can be provided on one or both sides of the metal component as a current collector to improve the electrical properties of the anode electrode.

[0009] According to another aspect of the invention, the silicon-carbon composite material may, for example, comprise at least one surface coating on a surface area not in contact with the metal component.

[0010] By providing at least one surface coating (e.g., a first surface coating), the chemical and mechanical stability of the coated silicon-carbon composite material and the chemical and mechanical stability of the anode electrode having such a material are improved. In particular, the surface coating can be applied by chemical vapor deposition (e.g., an atomic layer deposition process). Such a surface coating can also be applied to a silicon-carbon composite material having a complex or uneven surface geometry.

[0011] When the at least partially applied first surface coating is formed as a layer having a thickness of 0.1 nm to 1 μm, lithium ions for reversible lithium insertion can bypass the first surface coating without significantly reducing the corresponding kinetics.

[0012] According to another embodiment, the first surface coating comprises a metal oxide formed from at least one or more of the elements B, Al, Si, Zr, Nb, W and / or Li. For example, a suitable metal oxide may be formed as Al 2 O 3 and / or LiAlO 2 .

[0013] In another embodiment, a suitable metal oxide may be formed as ZrO 2 or / and Li 2 ZrO 3 , or Al 2 O 3 、ZrO 2 and a mixture of lithium aluminum oxide and lithium zirconium oxide.

[0014] Suitable surface coatings may be applied by an atomic layer deposition (ALD) process of trimethylaluminum and water or oxygen at a temperature between 100°C and 450°C followed by two or more ALD cycles, followed by optionally reacting the resulting aluminum oxide and aluminum hydroxide with a lithium compound such as Li-N(SiMe 3 ) 2 ) to chemically react to form a lithiated metal oxide. This coating can also be applied in combination with thermal exposure and / or in combination with a catalyst. In another embodiment, the metal oxide compound (Al 2 O 3 、Zr(OH) 4 、ZrO(OH) 2 ) is mixed with a lithium compound, followed by a heat treatment step at a temperature above 200°C to apply the surface coating.

[0015] In another embodiment, the first surface coating covers at least 50% of the surface area of ​​the silicon-carbon composite material. Thus, most of the surface area of ​​the silicon-carbon composite material can be protected by the first surface coating.

[0016] When the surface area of ​​the silicon-carbon composite is at least partially covered by the first surface coating and at least partially covered by the second surface coating, the silicon-carbon composite can have additional protection. Preferably, the second surface coating is at least partially applied above the first surface coating and / or applied next to the first surface coating. The second surface coating can provide additional control of the chemical and mechanical stability of the silicon-carbon composite.

[0017] Based on one embodiment of the silicon-carbon composite material, the second surface coating is formed as a carbon coating. When the silicon-carbon composite material is used in the electrode, this second surface coating can cause the silicon-carbon composite material to have a reduced resistance in the transition region between the second surface coating and the current collector or metal. In addition, this second surface coating can increase the conductivity within the silicon-carbon composite material layer. In another embodiment, an additional step can be applied to dry the silicon-carbon composite material with a dry atmosphere (O 2 、N 2 or a mixture thereof) to further passivate the surface area or the silicon-carbon composite.

[0018] In another embodiment of the silicon-carbon composite material, the silicon-carbon composite material has a 2 / g to 30m 2 / g, more preferably within the range of 4m 2 / g to 10m 2 / g range of surface area. 2m 2 / g, 30m 2 / g, 4m2 / g and 10m 2 Suitable boundaries of 100 μm / g may also form part of the defined range. Thus, the first surface coating and / or the second surface coating may be effectively applied to the silicon-carbon composite material having an increased surface area due to its porous carbon support.

[0019] Based on another embodiment of the silicon-carbon composite material, the silicon-carbon composite material includes lithium. In addition, the first surface coating may also include lithium in the form of a metal oxide. For example, the first surface coating may include a metal oxide formed of Li, especially in addition to Al. 2 O 3 In addition, the first surface coating may also contain a metal oxide formed by Li. Particularly preferably, the first surface coating may contain Al 2 O 3 , AlO(OH) and LiAlO 2 The mixture can act as a channel for lithium ions during reversible lithium insertion between the electrolyte and the silicon-carbon composite material. Therefore, the kinetics of lithium ions passing through the first surface coating and / or the second surface coating can be improved.

[0020] According to another aspect of the present invention, a method for manufacturing a surface-coated silicon-carbon composite material is provided. In the method steps, a porous carbon support having micropores and mesopores is provided. Si and at least one other compound (which contains at least one of Fe, Al, Ni, W and / or Ti) are introduced into the micropores and mesopores of the porous carbon support by chemical vapor infiltration to form a silicon-carbon composite. At least one surface coating is applied to the surface area of ​​the silicon-carbon composite to form a surface-coated silicon-carbon composite material, wherein at least one surface coating contains aluminum oxide or zirconium oxide and at least partially covers the surface area of ​​the silicon-carbon composite material.

[0021] By providing a surface coating comprising aluminum oxide or zirconium oxide, the silicon-carbon composite material can be protected from undesirable chemical reactions (such as uncontrolled oxidation processes). In particular, when manufacturing a battery cell or electrochemical energy storage device, an electrode comprising a surface-coated silicon-carbon composite material will provide improved chemical stability and reduce the possibility of undesirable chemical reactions due to at least a partial surface coating.

[0022] In one embodiment, at least one surface coating of the surface region of the silicon-carbon composite material is applied by a vapor deposition method. Thus, methods such as atomic layer deposition or molecular layer deposition can be performed to provide a surface coating with a controlled and uniform layer thickness.

[0023] In another embodiment, at least one surface coating is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a processed compound surface; wherein the processed compound surface is treated with moisture or oxygen or ozone to form at least one surface coating. Such materials for forming the processed compound surface are widely used and can therefore be provided in a cost-effective manner. For example, trimethylaluminum can be used to form the processed compound surface.

[0024] The surface coating of the surface region of the silicon-carbon composite material and / or the silicon-carbon composite material is formed to have a lithium content. Therefore, the silicon-carbon composite material can be pre-charged with lithium ions for use in an electrochemical energy storage device. 2 O 3 In addition to lithium compounds, lithium (such as LiAlO 2 or Li 2 ZrO 3 、LiNbO 3 ), channels for accelerating lithium ion exchange between the electrolyte and the silicon-carbon composite material of the electrode can be introduced.

[0025] According to another embodiment, the surface coating of the surface region of the silicon-carbon composite material comprises a metal oxide formed from at least one of the elements B, Al, Si, Zr, Nb, W and / or Li. Thus, in the case of atomic layer deposition or molecular layer deposition, the metal oxide is used as a precursor. An alternative or additional precursor may be formed as ZrO 2 、TiO 2 、Al 2 O 3 、SiN x 、TaN x In addition, Nb(OEt) can be introduced 5 or Li-N(SiMe 3 ) 2 The method for making a surface-coated silicon-carbon composite material includes a variety of possible materials for adjusting the chemical and mechanical properties of the surface coating.

[0026] In another embodiment, during the formation of the surface coating of the surface coating region of the silicon-carbon composite, a temperature in the range of 15° C. to 550° C. is applied to the silicon-carbon composite and the surface coating. Thus, methods such as thermal atomic or molecular layer deposition or plasma enhanced atomic or molecular layer deposition are suitable for manufacturing the surface-coated silicon-carbon composite.

[0027] According to another embodiment, the following treatment is repeated at least once: treating the silicon-carbon composite material with a metal alkoxide or a metal amide or an alkyl metal compound to form a processed compound surface, and treating the processed compound surface with moisture or oxygen or ozone. Thus, it is possible to ensure that a uniform coating is formed on the surface area of ​​the silicon-carbon composite material without leaving any unwanted processed compound (e.g., AlCH 3 ) traces.

[0028] The manufacturing process can be accelerated if a temperature in the range of 15°C to 550°C is applied during the treatment of the processed compound with moisture, oxygen or ozone.

[0029] According to another aspect of the present invention, a method for manufacturing at least one anode electrode is provided. In one step, a silicon-carbon composite mixture is mixed with at least one carbon. In another step, the silicon-carbon composite mixture is mixed with at least one aqueous binder solution and / or at least one non-aqueous binder solution to form an electrode paste. In addition, the electrode paste is at least partially applied to at least one surface of a conductor foil or a current collector. Then, the conductor foil to which the electrode paste is applied is dried at a temperature of 100° C. to 140° C. to form at least one anode electrode.

[0030] As adhesive, styrene-butadiene glue / carboxymethyl cellulose (CMC / SBR) blends, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA) can be used. In alternative embodiments, adhesive is formed as fluoropolymer such as polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), polyethylene tetrafluoroethylene (ETFE), polyvinyl fluoride (PVF), polyethylene trifluorochloroethylene (ECTFE), polyvinylidene fluoride (PCDF), polytrifluorochloroethylene (PCTFE), trifluoroethanol, or at least one of these materials and a combination of at least one other material. In another embodiment, adhesive is a copolymer of polyimide or polyacrylic acid and styrene-butadiene. Other possible adhesives can be formed as methyl methacrylate or polyvinylidene fluoride.

[0031] The surface coating step may be performed after the electrode paste drying process, or the silicon-carbon composite material may be provided in an already surface-coated form.

[0032] Another aspect of the present invention provides an electrochemical energy storage device, in particular in the form of a lithium ion battery. The electrochemical energy storage device comprises at least one anode electrode according to the present invention, at least one cathode electrode, a separator between the cathode electrode and the anode electrode, and an electrolyte containing lithium ions. Preferably, the cathode electrode comprises a transition metal oxide.

[0033] By utilizing an anode electrode having a surface-coated silicon carbon material, the dry room environment requirements for manufacturing an electrochemical storage device can be reduced because the anode electrode surface is protected.

[0034] Based on preferred applications, according to another aspect of the present invention, the method for manufacturing an anode electrode can also be performed based on a dry or semi-dry silicon-carbon composite mixture.

[0035] In a first step, a dry silicon-carbon composite mixture is provided, which is combined with a binder powder and contains graphite particles and / or carbon black particles. The binder powder may be formed as a PTFE powder.

[0036] Optionally, 5% to 10% ethylene carbonate may be added to the mixture.

[0037] Then, the silicon-carbon composite material mixture combined with the binder powder is at least partially applied to at least one surface of the conductor foil or the current collector by calendaring. In another step, at least one surface coating is applied to the surface area of ​​the silicon-carbon composite material to form a surface-coated silicon-carbon composite material, wherein the at least one surface coating comprises aluminum oxide or zirconium oxide and at least partially covers the surface area of ​​the silicon-carbon composite material.

[0038] The conductor foil coated with the dried or semi-dried electrode paste is then dried at a temperature of, for example, 100° C. to 140° C. to form at least one anode electrode. In another aspect, a use of a silicon-carbon composite material in an anode electrode is disclosed, wherein the silicon-carbon composite material comprises a porous carbon support, the porous carbon support comprising micropores and mesopores and having a total pore volume of not less than 0.5 cm 3 / g; the silicon content is 30% to 70%; and the silicon-carbon composite material includes a surface coating that is at least partially applied, which forms a surface coating area on the surface area of ​​the silicon-carbon composite material, and the surface coating area includes at least one or more elements of Li, B, Al, Si, P, Ti, Zr, Nb and / or W.

[0039] In another embodiment, the thickness of the surface coating on the silicon-carbon composite material is in the range of 0.1 nm to 0.1 μm.

[0040] In another embodiment, the surface coating on the silicon-carbon composite material comprises a metal oxide formed from at least one or more of the elements Li, B, Al, Si, Zr, Nb, and W.

[0041] In another embodiment, the surface coating area of ​​at least one surface coating covers greater than 50% of the surface area of ​​the silicon-carbon composite material.

[0042] In another embodiment, the silicon-carbon composite comprises a further surface coating or a second surface coating located on top of the first surface coating, such that the first surface coating and the second surface coating at least partially form a surface coating region.

[0043] In another embodiment, the other surface coating or the second surface coating is a carbon coating.

[0044] In another aspect, use of an anode electrode in an electrochemical energy storage device of the present invention is provided.

[0045] The present disclosure will be described in more detail below based on the exemplary embodiments shown in the accompanying drawings: BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A schematic diagram of a method for manufacturing a surface-coated silicon-carbon composite material according to an embodiment of the present invention is shown,

[0047] Figure 2 An exemplary electrochemical energy storage device having an electrode anode according to one embodiment of the present invention is shown, the electrode anode comprising a surface-coated silicon-carbon composite material, and

[0048] Figure 3 An exemplary electrochemical energy storage device having an electrode anode including a surface-coated silicon-carbon composite material according to another embodiment of the present invention is shown. DETAILED DESCRIPTION

[0049] In the drawings, the same reference numerals represent similar elements. The sizes and relative positions of the elements in the drawings are not necessarily drawn to scale, and some elements are enlarged and placed to improve the readability of the drawings. In addition, the specific shapes of the drawn elements are not intended to convey any information about the actual shape of the specific elements, but are only selected for ease of identification in the drawings.

[0050] Unless the context requires otherwise, in this specification and claims, the term "comprise" and variations thereof, such as "include" and "contain" should be interpreted in an open, inclusive sense, i.e., "including but not limited to". Unless otherwise stated, in this specification, any concentration range, percentage range, ratio range or integer range should be understood to include any integer value within the range, and, where appropriate, fractions thereof (e.g., one-tenth and one-hundredth of an integer). Unless otherwise stated, the terms "about" and "approximately" as used herein mean ±20%, ±10%, ±5% or ±1% of the range, value or structure. It should be understood that the terms "a" and "an" as used herein refer to "one or more" of the listed components. The use of alternatives (such as "or") should be understood to mean one, two, or any combination thereof.

[0051] References in this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of the present disclosure. Therefore, the phrases "in one embodiment" or "in an embodiment" appearing in various places in this specification do not necessarily all refer to the same embodiment. Furthermore, in one or more embodiments, the particular features, structures, or characteristics may be combined in any suitable manner.

[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. As used in the specification and claims, the singular forms "a", "an", and "the" include plural references unless the context clearly dictates otherwise.

[0053] The term "carbon part" in silicon-carbon composites refers to a material or substance consisting of or at least containing carbon. In this regard, carbon materials can include high purity, amorphous and crystalline materials. The carbon material can be activated carbon, pyrolyzed dry polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, activated dry polymer gel, activated polymer cryogel, activated polymer xerogel, activated polymer aerogel or a combination thereof. In another embodiment, carbon can be produced by pyrolysis of coconut shells or other organic wastes. In this regard, polymers are molecules containing more than two repeating structural units. Porous carbon (also referred to as porous carbon materials) has the advantages of being generally easy to produce, generally low in impurity content and large in pore volume. Therefore, porous carbon exhibits good electrical conductivity and high mechanical and chemical stability. In one embodiment, the carbon material has a high micropore volume ratio. Typically, porous carbon has a pore space, also referred to as a pore volume, wherein the pore space is a group of voids (pores) in carbon that can be filled with gas or fluid. In this regard, the properties and methods of making porous carbon are described in the prior art, such as U.S. Publication No. 2017 / 0015559, the entire disclosure of which is hereby incorporated by reference in its entirety for all purposes.

[0054] The Si portion of the silicon-carbon composite material may be pure silicon or a material composition containing silicon. For example, the Si portion may be at least one alloy. The alloy may be a silicon-titanium alloy (Si-Ti), a silicon-iron alloy (Si-Fe), or a silicon-nickel alloy (Si-Ni). In another embodiment, the Si portion may be composed of a P dopant, an As dopant, or an N dopant. The P dopant is typically a phosphorus dopant, the As dopant is typically an arsenic dopant, and the N dopant is typically a nitrogen dopant.

[0055] Figure 1 A schematic diagram of a method 1 for manufacturing a surface-coated silicon-carbon composite material 10 according to one embodiment of the present invention is shown.

[0056] In step 2 of the first method, a porous carbon support having micropores and mesopores is provided. The shapes and sizes of the porous carbon support and the silicon-carbon composite material 10 are shown for the purpose of illustrating method 1. The final shapes and sizes of the materials used may vary depending on the requirements.

[0057] In a further method step 3 , Si and optionally at least one further compound comprising at least one of Fe, Al, Ni and / or Ti are introduced into the micropores and mesopores of the porous carbon support by chemical vapor infiltration to form a silicon-carbon composite material.

[0058] In a further method step 4 , at least one surface coating 11 is applied to a surface region of the silicon-carbon composite material 10 to form a surface-coated silicon-carbon composite material.

[0059] At least one surface coating 11 contains aluminum oxide or zirconium oxide and covers at least a portion of the surface area of ​​the silicon-carbon composite material 10. In the exemplary embodiment, at least one surface coating 11, 12 covers the entire surface area of ​​the silicon-carbon composite material 10 in order to explain the principle.

[0060] In the illustrated embodiment, the surface region of the silicon carbon composite 10 is covered with trimethylaluminum TMA. During exposure of the surface region to trimethylaluminum, the trimethylaluminum dissociatively chemisorbs on the surface region of the silicon carbon composite 10, and any remaining gas phase trimethylaluminum can be easily removed.

[0061] The dissociative chemisorption of trimethylaluminum (TMA) resulted in the formation of AlCH 3 The surface of the processed compound is covered with water H 2 O or oxygen O 2 or ozone 3 The substrate is treated to form at least one surface coating layer, namely, the first surface coating layer 11 in the example.

[0062] The first surface coating 11 is made of Al 2 O 3 Molecular composition, because the treatment results in CH 3 A chemical reaction occurs. Such coatings can be provided by atomic layer thermal deposition, which also requires elevated temperatures, for example to 450°C.

[0063] In an optional step 5, the first surface coating 11 may be Li-N (SiMe 3 ) 2 The treatment is combined with heating to modify the first surface coating 11 into a modified first surface coating 11' so that it has, in addition to Al 2 O 3 The molecule also contains LiAlO 2 Such lithium-containing molecules can increase the kinetics of Li ions passing through the modified first surface coating 11 '.

[0064] In a further step 6, a second surface coating 12 may be applied on top of the first surface coating 11. In an exemplary embodiment, the second surface coating 12 consists of carbon C. Prior to such passivation by the second surface coating 12, the material may be heated in order to dissipate remaining binders and / or solvents (e.g. ethylene or propylene).

[0065] Figure 2A cross-sectional view of an exemplary electrochemical energy storage device 100 is shown, which has an electrode anode 110, wherein the electrode anode 110 includes Figure 1 The surface-coated silicon-carbon composite material 10 is manufactured by the method shown.

[0066] The electrochemical energy storage device 100 is formed as a lithium-ion battery cell. The electrochemical energy storage device 100 comprises at least one anode electrode 110, at least one cathode electrode 120 and a separator 130 arranged between the cathode electrode 120 and the anode electrode 110. The cathode electrode preferably contains a transition metal oxide.

[0067] In addition, an electrolyte 140 containing lithium ions is also provided in the battery housing 150 of the electrochemical energy storage device 100. The electrochemical energy storage device 100 may be formed as a bag-shaped lithium-ion battery cell. Therefore, the battery housing 150 may be formed as an aluminum bag. The anode electrode 110, the cathode electrode 120 and the separator 130 are also arranged in the battery housing 150. It is worth noting that Figure 2 A simplified cross-sectional view is shown. The anode electrode 110, cathode electrode 120 and separator 130 are typically formed in multiple layers that are rolled or folded to optimize packaging and increase the possible surface area of ​​the electrolyte 140. In the illustrated example, only one layer of the components is visible for illustration purposes.

[0068] Both sides of the anode electrode 110 are coated with the surface-coated silicon-carbon composite material 10. The surface coating 11 of the surface-coated silicon-carbon composite material 10 is applied at the surface area of ​​the silicon-carbon composite material 10 that is not in contact with the current collector 111 of the anode electrode 110.

[0069] By utilizing an anode electrode 110 having a surface-coated silicon-carbon material 10, the requirements for a dry room environment in manufacturing an electrochemical energy storage device 100 can be reduced. In particular, during the filling of the electrolyte 140 into the battery housing 150, chemical interactions of the electrode anode with contaminants can be reduced or prevented due to surface protection by the surface coating 11.

[0070] Figure 3 Another exemplary electrochemical energy storage device 100 is shown. The electrochemical energy storage device 100 includes an electrode anode 110 having a surface-coated silicon-carbon composite material 10. Figure 2 In contrast to the embodiment shown, the surface coating 11 of the silicon-carbon composite material 10 is applied to a partial surface area of ​​the silicon-carbon composite material 10 , so that a partial surface area of ​​the silicon-carbon composite material 10 remains free of the surface coating 11 .

Claims

1. A silicon-carbon composite material (10, 11), comprising: - porous carbon scaffolds containing micropores and mesopores with a total pore volume greater than 0.5 cm 3 / g; - a silicon content between 30% and 70%, inclusive; and - a surface region having an at least partially applied first surface coating (11), which comprises at least one element from the group consisting of Li, B, Al, Si, P, Ti, Zr, Nb and / or W.

2. The silicon-carbon composite material according to claim 1, wherein: The at least partially applied first surface coating (11) is formed as a layer, the layer of the surface coating having a thickness of 0.1 nm to 1 μm.

3. The silicon-carbon composite material according to claim 1 or 2, wherein: The first surface coating (11) comprises a metal oxide formed of at least one or more of the elements B, Al, Si, Zr, Nb, W and Li.

4. The silicon-carbon composite material according to any one of claims 1 to 3, wherein The first surface coating (11) contains a metal oxide formed from Li, in particular contains a metal oxide formed from Li in addition to Al2O3.

5. The silicon-carbon composite material according to any one of claims 1 to 4, wherein The first surface coating (11) covers at least 50% of the surface area of ​​the silicon-carbon composite material (10).

6. The silicon-carbon composite material according to any one of claims 1 to 5, wherein: The surface area of ​​the silicon-carbon composite material (10) is at least partially covered by the first surface coating (11) and the second surface coating (12), wherein the second surface coating (12) is at least partially applied on top of the first surface coating (11) and / or next to the first surface coating (11).

7. The silicon-carbon composite material according to claim 6, wherein: The second surface coating (12) is formed as a carbon coating.

8. The silicon-carbon composite material according to any one of claims 1 to 7, wherein: The silicon-carbon composite material (10) has a 2 / g to 30m 2 / g range, especially in the 4m 2 / g to 10m 2 / g range of surface area.

9. The silicon-carbon composite material according to claim 1 to claim 8, wherein: The silicon-carbon composite material (10) contains lithium.

10. A method (1) for producing a surface-coated silicon-carbon composite material (10) according to any one of claims 1 to 9, comprising: - providing porous carbon scaffolds having micropores and mesopores, - introducing Si and optionally at least one additional compound into the micropores and mesopores of the porous carbon support by chemical vapor infiltration to form a silicon-carbon composite (10), the additional compound comprising at least one of Fe, Al, Ni, W and / or Ti, - applying at least one surface coating (11, 12) to a surface region of the silicon-carbon composite material (10) to form a surface-coated silicon-carbon composite material (10), wherein the at least one surface coating (11) comprises aluminum oxide or zirconium oxide and at least partially covers the surface region of the silicon-carbon composite material (10).

11. The method according to claim 10, wherein: The at least one surface coating (11, 12) of the surface region of the silicon-carbon composite material is applied by a vapor deposition method.

12. The method according to claim 10 or 11, wherein: The at least one surface coating is treated with a metal alkoxide or a metal amide or an alkyl metal compound to form a processed compound surface; wherein the processed compound surface is treated with moisture or oxygen or ozone to form at least one first surface coating (11).

13. The method according to any one of claims 10 to 12, wherein: The first surface coating (11) of the surface region of the silicon-carbon composite material (10) and / or the silicon-carbon composite material (10) is formed of lithium.

14. The method according to any one of claims 10 to 13, wherein: The first surface coating (11) of the surface region of the silicon-carbon composite material (10) comprises a metal oxide formed from at least one of the elements B, Al, Si, Zr, Nb, W and / or Li.

15. The method according to any one of claims 10 to 14, wherein: During the formation of the first surface coating (11) of the surface coating region of the silicon-carbon composite material, a temperature in the range of 15° C. to 550° C. is applied to the silicon-carbon composite material (10) and the first surface coating (11).

16. The method according to claim 12, wherein: The silicon-carbon composite material (11) is treated with a metal alkoxide, a metal amide or an alkyl metal compound to form a processed compound surface, and the processed compound surface is treated with moisture or oxygen or ozone at least once.

17. The method according to any one of claims 12 to 16, wherein: During the treatment of the processed compound with moisture or oxygen or ozone, a temperature in the range of 15°C to 550°C is applied.

18. An anode electrode (110) comprising a surface-coated silicon-carbon material (10) having at least one surface coating (11, 12) according to any one of claims 1 to 9.

19. A method for manufacturing at least one anode electrode (110) according to claim 18, comprising: - mixing the silicon-carbon composite with at least one carbon, - combining the silicon-carbon composite mixture with at least one aqueous binder solution and / or at least one non-aqueous binder solution to form an electrode paste, - applying the electrode paste at least partially on at least one surface of a conductor foil (111), - Drying the conductor foil (111) with the electrode paste applied thereto at a temperature of 100°C to 140°C to form at least one anode electrode (110).

20. A method for manufacturing at least one anode electrode (110) according to claim 18, comprising: - mixing the dry or semi-dry silicon-carbon composite mixture with at least one carbon; in The mixture is combined with a binder powder and contains graphite particles and / or carbon black particles; - applying the silicon-carbon composite mixture combined with the binder powder at least partially on at least one surface of a current collector formed as a conductor foil (111) by calendering; - Drying the conductor foil (111) coated with the mixture at a temperature of 100°C to 140°C to form at least one anode electrode (110).

21. An electrochemical energy storage device (100), in particular in the form of a lithium-ion battery, comprising: - at least one anode electrode (110) according to claim 18; - at least one cathode electrode (120), wherein the cathode electrode (120) comprises a transition metal oxide; - a separator (130), the separator (130) being arranged between the cathode electrode (120) and the anode electrode (110); and - an electrolyte (140), said electrolyte (140) comprising lithium ions.

Citation Information

Patent Citations

  • Novel methods for sol-gel polymerization in absence of solvent and creation of tunable carbon structure from same

    US20170015559A1